UNTRADITIONAL WAYS OF REVEALING OF CREATIVE POTENTIAL OF FUTURE PAINTER-TEACHER (Pedagogy of Higher and Secondary Education, 2022)
The perspectives of utilization of untraditional methods and ways of actuating and revealing of a personality’s creative potential, which is grounded on a using of visual means, are considered in the article. On the basis of examining of spread untraditional strategies of stirring up and developing of creative abilities of a personality the way’s of perfection of professional training of art departments students of teachers training institutes are observed.